Project-Based Learning in Chemistry: Improving Laboratory Skill through Gravimetric Alkaloid Analysis of Local Natural Materials - Nurfatimah Sugrah; Khusna Arif Rakhman; Nur Jannah Baturante; Indra Cipta; Ni Made Wiratini; Agung Abadi Kiswandono; Dimas Saman (PAEDAGOGIA, 2026)
Conventional chemistry laboratory instruction often separates theoretical understanding from practical activities, limiting students’ opportunities to develop integrated knowledge and laboratory skills. Project-Based Learning (PjBL) has been widely recognized as an effective approach to promote active, collaborative, and experiential learning in chemistry education. This study implemented PjBL in an analytical chemistry laboratory course involving 21 students, with samples divided into four groups. Students conducted projects on the isolation and gravimetric determination of alkaloids from local natural materials in North Maluku. Learning outcomes were evaluated through observations of laboratory activities, data analysis, collaboration, and research poster presentations. The imple mentation of PjBL showed high student participation (91.7%) and improved laboratory skills, including chemical handling, gravimetric analysis, data management, and scientific communication. Students successfully produced research reports and posters, while most participants reported enjoyable learning experiences, increased motivation, and improved collaboration and problem-solving skills. Research-based PjBL effectively integrates theoretical knowledge and laboratory practice, while supporting the development of laboratory competence, collaborative learning, and scientific communication skills among chemistry education students.